The effect of virtual mode deep breathing intervention on anxiety among primary school children during COVID-19 pandemic - Shafawi, Nur Syafiqah Syahrain Mohd (2021)
CODID-19 pandemic that hits the world in 2019 impacts people in various aspects of life including the psychological aspect. It has induced anxiousness among people due to the uncertainty and fear of the pandemic and it is not exclusive towards adults only. Concurrently, a national survey suggested the prevalence of anxiety among children in Malaysia is alarming. Due to that, the current study was conducted to investigate the effect of deep breathing on the level of anxiety among primary school children via virtual-based intervention as well as to examine its feasibility. A pre-test, post-test randomised controlled design was carried out wit 28 students at a primary school in Kelantan. The students in the intervention group participated in a four-week deep breathing intervention with weekly meetings with the researcher, whereas the participants in the control group did not receive any intervention. A repeated-measures ANOVA was conducted and showed no significant difference between the intervention and control group after four-week of intervention. However, a paired sample t-test indicated a significant difference in the level of state anxiety within the participants in the intervention group and no significant difference for the control group. In contrast, there was no significant difference in the level of trait anxiety for both groups. Despite the primary findings showed no significant result, there was a trend of declination for both state and trait anxiety, particularly for state anxiety. Thus, it could be suggested that the deep breathing exercise could help in reducing the level of anxiety and it is simple, quick, and easy to be learned as well as applied by the children via virtual mode.